Experiences Of Parents With Preterm Children In Accra, Ghana: Coping Resources Parents Use. - Opoku-Mensah, A.K. (University Of Ghana, 2021)
ABSTRACT The continuous rise in preterm births in Ghana has led to the country’s inability to achieve Millennial Development Goal 4 – which is, reducing the mortality rate of children under age five. Unfortunately, the exact cause of preterm birth is still unknown. Preterm birth is associated with poor developmental outcomes and low chances of survival for children, leaving parents and families of the affected children with mixed feelings and stress. Complications associated with preterm infants (such as their vulnerability to infections, inability to breastfeed and low weight) cause parents to fear losing the baby. This study investigated the coping resources available to parents with preterm infants at home. The study employed a qualitative approach that is, using an exploratory descriptive design and data collected at one point in time. The study location was the Department of Child Health at the Korle-Bu Teaching Hospital (KBTH). A total of 19 mothers, purposively selected, were used for the study. Data was analyzed using thematic content analysis. The predetermined themes data was organized around were: mothers’ experiences during hospitalization, mothers’ post-NICU experiences, coping resources parents used and support systems. 17 sub-themes emerged from the interviews conducted. The findings showed that resources such as money, taking time off work, faith, space, inner strength, among others made caring for their preterm less difficult and ensured the survival of their infants. Based on the findings, it was recommended that the government should add most Neonatal and Intensive Care Unit (NICU) charges to the National Health Insurance Scheme (NHIS) and the Ghana Under-five Health Policy. The findings of this study meaningfully add up to existing literature on preterm birth in Ghana.
MPhil. Home Science
Keywords: Preterm; Coping; Resources; Korle-Bu Teaching Hospital; Experiences; ABC-X Model; NICU